Alopecia resembling an 'undercut hairstyle' in a child with acute lymphoblastic leukemia at presentation - Sidharth Totadri; Peyam Srinivasan; Deepak Bansal (Elsevier, 2018)
Alopecia is unusual at presentation in children with cancer. Alopecia neoplastica has been described in adults with metastatic carcinoma and melanoma. Additionally, alopecia may accompany lymphoma as a paraneoplastic phenomenon. We describe a child with acute lymphoblastic leukemia, who presented with a distinct pattern of alopecia involving the scalp. The child had not received any chemotherapy prior. Keywords: Childhood leukemia, Dermatological manifestation, Hair loss, Malignant alopecia, Leukemic alopecia